Permanent Pixels: Building blocks for the longevity of digital surrogates of historical photographs - van Horik, Rene (DANS studies in digital archiving, 2005)
This book is about the longevity of digital surrogates of historical photographs. The preservation of digital photos is considered in the context of long-term access to digital objects in general. There is a general view among archivists, librarians and museum professionals that analogue originals and their digital counterparts are closely related. The features of a digital surrogate, such as a scanned historical photograph, are based on an assessment of the analogue original as well as the intended function of the digital surrogate, also in the long term. This gives the digital objects to be preserved a very specific character that justifies the scope of this research on the longevity of a specific digital data object. The focus on the longevity of digital surrogates of historical photographs enables the investigation of available building blocks for digital preservation such as guidelines, procedures, tools, standards, strategies and methods to enable long-term access to digital data objects. This study examines in detail the role of digital preservation strategies, file format standards, content format standards, metadata schemas and other building blocks for the realisation of durable digital surrogates of historical photographs.